Detection of porcine DNA in food using direct asymmetric PCR and catalyzed hairpin assembly fluorescent biosensor: A novel assay for halal food analysis. (September 2022) - Prachugsorn, Apinya; Thanakiatkrai, Phuvadol; Phooplub, Kittirat; Ouiganon, Sirirat; Sriaead, Yossawadee; Thavarungkul, Panote; Kanatharana, Proespichaya; Buranachai, Chittanon; Kitpipit, Thitika
Abstract: Adulteration of halal-certified food with pork are often reported. Using direct PCR results in cost- and time-saving benefits, and allows flexibility in amplicon detection. Here, we aimed to develop and validate a novel, direct asymmetric PCR and catalyzed hairpin assembly fluorescent biosensor (daPCR-CHA-FB) with a portable LED lightbox for naked eye detection of porcine DNA in raw and processed food. We tested the assay's reproducibility, specificity, sensitivity, real-world applicability, and single-blind performance. Using only 1 mm 3 samples, reproducibility test with 38 raw pork samples showed 2.6% false negative rate and 0.0% false positive rate. The lowest detection limits were 0.01 ng for porcine DNA and 0.1% for binary pork-and-beef mixture. No cross-reaction with 16 other species was observed. One-hundred market samples showed no false negative for pork-listed samples, while two samples declared as non-pork showed a positive reaction. The assay was simple, sensitive, specific, safe, and robust. It could be used by law enforcement agencies and small-scale laboratories to investigate contamination and adulteration of halal foods. Highlights: A novel assay called daPCR-CHA-FB was optimized and validated for pork detection. Direct asymmetric PCR omits DNA extraction, saving time and cost, and yields ssDNA. Biosensor-based DNA detection (CHA-FB) is observable by naked eye. Developed assay is highly reproducible, specific, sensitive, and robust. Two market samples declared as non-pork showed a positive reaction to our assay.